Emotional commitment in public political internet message boards - Kleinke, Sonja (Journal of language and social psychology, 2008)
This study focuses on political discourse among laypersons in public Internet-based political discussion groups and analyzes emotive communication as a product, which is viewed as a continuum including both emotional attachment and emotional detachment. It analyzes 11,000 words of discussion in 180 contributions produced by a total of 65 participants of three political message boards with regard to a selected range of linguistic token features signaling emotional commitment. The results obtained are compared to their frequency in private conversation and newspaper registers to determine where the message boards range within the scale of related registers. The findings are discussed against the background of the framing conditions of political message board communication.
Gesehen am 03.09.2019